NADPH oxidase 2 mediates cardiac sympathetic denervation and myocyte autophagy, resulting in cardiac atrophy and dysfunction in doxorubicin-induced cardiomyopathy - Ma, Yuan; Zhao, Hui-Ping; Yang, Li-Guo; Li, Lu; Wang, Ai-Lin; Zhang, Xiao-Juan; Wang, Ke; Yang, Bin; Zhu, Zong-Feng; Zhang, Pei-Jun; Wang, Jia-Pu; Chi, Rui-Fang; et al. (Scientific reports, 2024)
Doxorubicin has been used extensively as a potent anticancer agent, but its clinical use is limited by its cardiotoxicity. However, the underlying mechanisms remain to be fully elucidated. In this study, we tested whether NADPH oxidase 2 (Nox2) mediates cardiac sympathetic nerve terminal abnormalities and myocyte autophagy, resulting in cardiac atrophy and dysfunction in doxorubicin-induced heart failure. Nox2 knockout (KO) and wild-type (WT) mice were randomly assigned to receive a single injection of doxorubicin (15 mg/kg, i.p.) or saline. WT doxorubicin mice exhibited the decreases in survival rate, left ventricular (LV) wall thickness and LV fractional shortening and the increase in the lung wet-to-dry weight ratio 1 week after the injections. These alterations were attenuated in Nox2 KO doxorubicin mice. In WT doxorubicin mice, myocardial oxidative stress was increased, myocardial noradrenergic nerve fibers were reduced, myocardial expression of PGP9.5, GAP43, tyrosine hydroxylase and norepinephrine transporter was decreased, and these changes were prevented in Nox2 KO doxorubicin mice. Myocyte autophagy was increased and myocyte size was decreased in WT doxorubicin mice, but not in Nox2 KO doxorubicin mice. Nox2 mediates cardiac sympathetic nerve terminal abnormalities and myocyte autophagy—both of which contribute to cardiac atrophy and failure after doxorubicin treatment.